Antimicrobial Growth Promoters and Salmonella spp., Campylobacter spp. in Poultry and Swine, Denmark - Evans, Mary C. (Centers for Disease Control and Prevention, 2003)
The use of antimicrobial growth promoters in Danish food animal production was discontinued in 1998. Contrary to concerns that pathogen load would increase; we found a significant decrease in Salmonella in broilers before and after slaughter of swine and pork and no change in the prevalence of Campylobacter in broilers.